Expansão do crédito para empresas e desenvolvimento econômico - Soares, Bruno Learth (2019)
We use a version of the neoclassical growth model with heterogeneous agents and financial frictions to evaluate the macroeconomic impacts of credit to firms in Brazil. The model is calibrated to match facts about Brazilian economy between 2007 and 2015, in order to conduct counterfactual exercises by changing parameters of the credit policy. The analysis suggests that the reduction of subsidies, or the end of earmarked credit programs, would decrease GDP because of the reduction in aggregate capital, but would increase productivity and wages.